Male and female Indonesian EFL undergraduate students’ metacognitive strategies in academic reading: planning, monitoring and evaluation strategies - Erina Andriani; Concilianus Laos Mbato (Journal on English as a Foreign Language, 2021)
Metacognitive strategies have been investigated as helping tools for students’ reading comprehension, but their use may vary between males and females. Though gender is an essential factor in language learning, few studies highlighted the influence of gender on the metacognitive reading strategy use by Indonesian students. To fill in the gap, this study investigated the use of metacognitive strategies during academic reading from a gender perspective. A mixed-method was adopted, with open-ended and close-ended questionnaires and a semi-structured interview used to gather the data. From the quantitative data analysis, the students used most metacognitive strategies to a high degree. The only significantly different strategy use was guessing meaning (F=0.232, p<0.05), where male students used it more often. From the qualitative data analysis, the female students used more strategy variations than the male students (20 and 18 strategy variations respectively).  The students shared some similar and some different reasons to use metacognitive reading strategies. The results suggested the gender influence on male students to make predictions. The findings from this research will prompt English teachers to introduce metacognitive strategies in reading through appropriate instructions and guidance to enable the students to implement and develop their metacognitive strategies in academic reading.